Unterscheiden sich Mathematiklehrkräfte an Grundschulen mit und ohne Fach-Lehrbefähigung hinsichtlich ihrer berufsbezogenen Überzeugungen? Ergebnisse aus TIMSS 2007 (mathematica didactica, 2021)
This article addresses the question of whether there are differences between out of-field and in-field teachers with regard to their profession-related beliefs – beliefs about teaching and personal convictions in mathematics. Findings of national and international research that examined the specific situation and beliefs of teachers without a formal qualification for a subject will be presented. Subsequently responses to questions about profession related beliefs and the participation in in-service training of mathematics teachers with and without a teaching certificate for the subject will be analysed using national data from the TIMS 2007 study.